2012
DOI: 10.7744/cnujas.2012.39.4.577
|View full text |Cite
|
Sign up to set email alerts
|

Polymorphisms of LEP, LGB and PRLR in water buffalo

Abstract: :The polymorphisms of several genes including Leptin (LEP), beta-lactoglobulin (LGB) and Prolactin receptor (PRLR) have been shown to affect milk composition traits in dairy cattle. But, the effects of these polymorphisms on the milk traits of Philippine water buffalo are still unclear. In the Philippines, buffalo are the major milk producers most of which are the Philippine carabao (PC), the American Murrah Buffalo (AMB) and Bulgarian Murrah Buffalo (BMB). The LEP, LGB and PRLR genes are considered to be asso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 15 publications
(13 reference statements)
1
5
0
Order By: Relevance
“…PCR-RFLP pattern using Eco91I of the target fragment showed that all the investigated buffaloes had CC genotype which was confirmed by direct sequencing. In agreement with the current results, some investigators confirmed the CC genotype as the only detected genotype among several river buffalo breeds [3,[8][9][10][11][12]. But in cattle, the frequencies of CT and TT genotypes were 34% and 8% (Liefers et al [4]), 47.03% and 9.13% [7], 38.8% and 2.4% [5], and 33% and 6% [6], respectively.…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…PCR-RFLP pattern using Eco91I of the target fragment showed that all the investigated buffaloes had CC genotype which was confirmed by direct sequencing. In agreement with the current results, some investigators confirmed the CC genotype as the only detected genotype among several river buffalo breeds [3,[8][9][10][11][12]. But in cattle, the frequencies of CT and TT genotypes were 34% and 8% (Liefers et al [4]), 47.03% and 9.13% [7], 38.8% and 2.4% [5], and 33% and 6% [6], respectively.…”
Section: Discussionsupporting
confidence: 90%
“…The alleles of G140A, G263A, and G379A SNPs in addition to 21 SNPs were found between in the leptin gene in the sequenced fragment of the Egyptian buffalo and the other buffalo breed records for the same gene in GenBank. The T allele of C32T intronic SNP was unique and was detected in Egyptian buffalo within this investigation only and was not detected in any buffalo records in Gen-Bank or previous studies on river buffalo [3,[8][9][10][11][12].…”
Section: Discussionmentioning
confidence: 49%
See 2 more Smart Citations
“…However, this polymorphism was found in the heterozygous state in only one sample of Italian buffalo, whereas the other animals showed a GG homozygote genotype (Orrù et al, 2007). The existence of an A allele was confirmed by DNA sequencing of 390 Murrah and Philippine Carabao buffaloes, with an allele frequency of 0.18 (Seong and Kong, 2012). Also, Kale et al, 2013 detected the same variation by SSCP in Murrah, Surti and Bhadawari, with a high allele frequency of 0.3.…”
Section: Introductionmentioning
confidence: 87%